Social history of street children in Lima - Roggenbuck, Stefan (1996)
The author presents a historical survey of street' children in Lima. He emphasizes the fact that Lima's colonial urban culture did not allow the articulation and development of this social phenomenon in past centuries as was the case in other Latin American cities such as Sao Pau/o (Brazil) and Bogotá (Colombia). In Lima street children first appeared in the twentieth century as a consequence of the processes of urbanization and modernization. The author describes in detail the recent history of childhood life on the streets of Lima including aspects of welfare work. Final/y he describes the real life of street children in the historical centre of Lima at the md of the eighties based on field research using modern sociological methods.